Biological screening of Amaranthus retroflexus L. (Amaranthaceae) - Amoli,Jamileh Salar (2009)
Bioassays are required for the determination of the total toxicity of Amaranthus retroflexus L. (Amaranthaceae) or "redroot pigweed". Therefore, the plant extract has been tested for bioactivity in Artemia salina and cytotoxicity against bovine kidney cells. The LD50 values for Artemia salina were measured at 1700 ppm. The bovine kidney cells were exposed to various concentrations of the plant extracts (100 ppm-0.1 ppm). After treating with 100 and 0.1 ppm for 24 h, the cells viability were reduced by about 49% and 35% respectively in MTT viability assay. The study confirmed that Amaranthus retroflexus has a cytotoxic effect and more specific to renal cells.